ANALISIS TATANIAGA SALAK PONDOH (Salacca edulis Reinw) DI DESA SIGEBLOG KECAMATAN BANJARMANGU KABUPATEN BANJARNEGARA - Agit Dwi Cahyo; Pujiharto Pujiharto; Watemin Watemin (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2016)
This research aimed to find out marketing system pattern channel, to find the marketing system so the margin on of marketing salak pondoh, and to know the farmer share. Method of this research used survey, 45 farmers and 10 trader salak pondoh as respondents take using purposive sampling. The research was conducted for four mount from April to July2016. Result of this research showed that there were five pattern of trading system salak pondoh, the margin trading for each pattern of trading system was so different in size affected by several factor such as length link of trading system, the cost of trading system, and marketing purposes, the prices received by farmers (farmer share) in every pattern trading system were different, it was affected by the sales price in urban farmers and the selling price level in last consumer. The biggest margin trading system was in the third pattern of trading system with total margin Rp.3.000 per kilogram, and the pattern or trading system having smallest margin was the smallest margin is the pattern trading system to 1 with a total the margin Rp. 1.000 per kilogram, the share received by farmers (farmer share) of trading system of salak pondoh in Sigeblog is the greatest pattern of trading system 1 with 76,7%, and the smallest is in a patern of trading system 3 with 52,4%.